1999
DOI: 10.1097/00001888-199907000-00017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a domestic violence interclerkship on the knowledge, attitudes, and skills of third-year medical students

Abstract: Participation in a short, focused DVI curriculum produced sustainable improvements in knowledge, attitudes, and skills that were successfully applied by third-year medical students to effective domestic violence screening. Interclerkships are an effective way to fit into the clinical curriculum those subjects that transcend the traditional biomedical domain and intersect all areas of medical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 0 publications
1
38
1
Order By: Relevance
“…The OSCE can effectively assess clinical performance and is used at all levels of medical education to evaluate clinical skills; it has been used at the end of core clerkships [6][7][8][9] and to measure skills in specific domains. [10][11][12] …”
mentioning
confidence: 99%
“…The OSCE can effectively assess clinical performance and is used at all levels of medical education to evaluate clinical skills; it has been used at the end of core clerkships [6][7][8][9] and to measure skills in specific domains. [10][11][12] …”
mentioning
confidence: 99%
“…There are other medical interview teaching interventions that have demonstrated success, but these are typically with a single skill set 22,23 with undergraduate medical students 25,43 or at single institutions. 8,9 Our teaching that utilizes learnercentered teaching methods requires a faculty well versed in teaching communication skills, but also adept at modifying his or her teaching to specific participant learning needs.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] A recent Cochrane Review underscored the need for clear descriptions of teaching methods for those developing communication skills programs. 21 To date, much of the published literature has focused on the teaching of skills pertaining to a single task of the interview, such as screening for domestic violence, 22 and delivering bad news. 23 One recent study implementing a broad curriculum in the third year at three US medical schools showed encouraging changes in medical students' communication skills as a result of the implemented curriculum.…”
mentioning
confidence: 99%
“…The University of Massachusetts model takes such an approach to domestic violence education in the clinical clerkship year, for example. 9 During two sessions, family physicians, paediatricians, gynaecologists, nurses and social workers present a comprehensive approach to domestic violence, addressing behaviours of both victims and perpetrators, as well as issues of safety in the home. Similarly, the American College of Obstetricians and Gynecologists (ACOG) has developed a module on female genital mutilation (FGM) for the training of interns and as a component of continuing medical education programmes.…”
Section: Delegated Modelmentioning
confidence: 99%